Global perspectives on the emerging trends in public diplomacy - KÖKSOY, ERGÜN; KAVOĞLU, SAMET (IGI Global, 2023)
Since the 20th century, when modern democracies gained strength, governments have been carrying out their domestic and foreign policies with the consent of society. For this reason, all organizations that seek to influence governments strive to make a name for themselves in the eyes of the public. Similarly, states also seek to establish a reputation and trust in the public opinion of a target country or within specific target communities through public diplomacy activities. As can be seen, notable studies and work on public diplomacy have been conducted for more than half a century, and the field has evolved. Public diplomacy emerged as an extension of developments in international relations and diplomacy, as a way for countries and governments to communicate and build relationships with the corresponding strategic bodies in other countries. Increasing political, economic, social, and cultural relations on a global scale have transformed diplomatic relations into an issue that encompasses societies and peoples, unlike in the past when they were limited to official relations between countries and governments. As the public face of diplomacy as we know it, we can describe it as an international actor’s attempt to navigate the international environment by building close relationships with foreign peoples. On the one hand, public diplomacy is a way for countries to transmit their policies, opinions, and values to other societies; on the other hand, it creates a suitable environment for nations and their peoples to build and foster intertwined relationships and mutual understanding. Thus, it supports international relations and communication in general and the implementation of a particular country’s foreign policy and national interests in particular. As an extension of this fact, the public diplomacy of countries revolves around their foreign policies and objectives and contributes to diplomacy and international processes. Many researchers have come to the same conclusion: foreign policy and diplomacy cannot achieve the desired results and be successful without the policies and applications of public diplomacy. xii Preface However, the public diplomacy literature is mainly USA-dominated due to its pioneering role in the emergence of the concept and its institutionalization. Perceptions and practices of public diplomacy in other countries also evolve under the influence of this experience. With this effect, each country determines its areas of practice and actors for public diplomacy, taking into account its power, sphere of influence, opportunities, and risks. Global Perspectives on the Emerging Trends in Public Diplomacy offers insights into the approaches taken by countries in different geographies and how they tailor their public diplomacy activities based on their unique opportunities and risks. By examining the practices of different countries, this book provides a global picture of public diplomacy activities and identifies emerging trends shaping the field. This book is indispensable for researchers, academics, undergraduate and postgraduate students, and non-governmental and governmental organizations seeking to improve their understanding of public diplomacy. The multiple perspectives offered in this book enable readers to understand how different countries approach public diplomacy and how these activities are evolving in the current global landscape. Global Perspectives on Emerging Trends in Public Diplomacy contains nine different chapters. The book contains the work of many authors, ranging from approaches to public diplomacy by countries and regions to studies and topics dealing with public diplomacy from different and current perspectives. It is noteworthy that, especially in the 2000s, the topic and policy of public diplomacy have gained prominence worldwide. Public diplomacy activities were seen as part of foreign policy and soft power issues and were often used to reinforce issues. Similarly, public diplomacy has been associated with current issues and phenomena such as the pandemic and new technologies.
Keywords: Sosyal ve Beşeri Bilimler; Kitle İletişimi ve Araçları; Social Sciences and Humanities; Mass Communications and Mass Media; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; İLETİŞİM; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; COMMUNICATION; İletişim; Sosyal Bilimler ve Beşeri Bilimler; Communication; Social Sciences & Humanities